Correlation of Cytohistlogical Expression and Serum Level of Ca125 in Ovarian Neoplasm - Chhanda Das; Madhumita Mukhopadhyay; Tarun Ghosh; Ashis Kumar Saha; Moumita Sengupta (Journal of Clinical and Diagnostic Research, 2014)
Context or Background: CA125 is a biomarker that has potential utility across the spectrum: risk assessment, early detection, diagnosis, prognosis, monitoring and therapy. Aims and Objectives: This study was conducted to establish the validity and reliability of correlation of CA125 serum level with immunochemistry expression in imprint cytology and tissues for diagnostic purpose. Materials and Methods: A prospective study was done on 50 cases of clinically and radiologically diagnosed ovarian tumor. Imprint smears were made intraoperatively from fresh samples and stained with M.G.G. stain for air dried smears and Papanicolaou stain for alcohol fixed smears. Stained smear was assessed and compared with subsequent histopathology report. Preoperative blood samples were obtained from all patients and sent for the assay of serum CA125 levels. Analysis of CA125 immunochemistry expression in imprint cytology and tissue was done and correlated with preoperative serum blood CA125 levels. Results: Significant positive correlation was found between elevated serum CA125 levels and cytohistological expression of CA125. Overall sensitivity was 100%, specificity was 86%, positive predictive value was 74% and negative predictive value 100%. Diagnostic accuracy was 90% with high statistical significance (p<0.001). Conclusion: We considered 35 U/mL as the cut-off value when evaluating serum CA125 ovarian cancer. Patients with high serum levels show good cytohistological expression.